Paparan Gas Anestesi Dan Dampaknya Terhadap Kesehatan Tenaga Medis Di Ruang Operasi Rumah Sakit TNI Dr. R. Soeharsono Banjarmasin: Pendekatan Kualitatif - Lestari, Puji Ayu Asri Sri; Endang Suprihati Ningsih (Jurnal Kesehatan Mahardika, 2025)
Waste anesthetic gas (WAG) exposure in surgical settings presents occupational health risks to medical personnel, potentially affecting the nervous, respiratory, and reproductive systems. Although safety protocols are available, implementation is often suboptimal, particularly in resource-limited facilities. Objective: This study aimed to explore the health impacts of anesthetic gas exposure on operating room staff at Dr. R. Soeharsono Military Hospital, Banjarmasin, by gaining an in-depth understanding of their perspectives, experiences, and perceived challenges. Methods: A phenomenological qualitative design was employed, with in-depth semi-structured interviews conducted with ten purposively selected operating room staff, including anesthesiologists, nurses, and technicians. Thematic analysis was used to identify patterns and key insights from participant narratives. Participants reported symptoms such as headaches, fatigue, nausea, and decreased concentration, which they associated with prolonged anesthetic gas exposure. While awareness of the risks was generally present, many cited limited ventilation, inadequate scavenging systems, and the absence of routine air quality monitoring. Institutional training and occupational health measures were also perceived as insufficient. Anesthetic gas exposure remains a significant occupational hazard in the surgical unit. Addressing this issue requires improving safety infrastructure, ensuring functional ventilation and scavenging systems, implementing regular air quality assessments, and providing ongoing training to protect the health of medical personnel.